2021
DOI: 10.3390/jcm10051099
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Using a Larger Forearm Artery for Percutaneous Coronary Interventions on Hand Strength: A Randomized Controlled Trial

Abstract: (1) Background: The exact mechanism underlying hand strength reduction (HSR) after coronary angiography with transradial access (TRA) or transulnar access (TUA) remains unknown. (2) Methods: This study aimed to assess the impact of using a larger or smaller forearm artery access on the incidence of HSR at 30-day follow-up. This was a prospective randomized trial including patients referred for elective coronary angiography or percutaneous coronary intervention. Based on the pre-procedural ultrasound examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…The follow-up was short but consistent with the short duration of the hospital stay. All of the procedures were performed from the radial artery, and we did not assess the ulnar artery in order to choose the dominant one, which might have influenced the outcomes [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The follow-up was short but consistent with the short duration of the hospital stay. All of the procedures were performed from the radial artery, and we did not assess the ulnar artery in order to choose the dominant one, which might have influenced the outcomes [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research shows that hand exercises can guide patients to perform functional exercises that can improve blood circulation in the upper limbs and increase blood flow in the radial artery and cephalic vein (Lewandowski et al, 2021). In the hand grip test after transradial study (HANGAR), a hand dynamometer applied to patients undergoing transradial PCI improved the recovery of hand strength and helped improve blood circulation in the limbs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research indicated that handgrip exercise with a dynamometer as a medium could guide patients to perform functional exercise and promote blood circulation in the upper limbs [ 12 ]. Furthermore, a previous study reported that handgrip dynamometers could promote blood circulation and increase the blood flow of the radial artery and cephalic vein [ 13 ]. In the Hand Grip test After Transradial (HANGAR) study, the hand dynamometer applied in patients who underwent transradial PCI promoted the recovery of hand strength [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the Hand Grip test After Transradial (HANGAR) study, the hand dynamometer applied in patients who underwent transradial PCI promoted the recovery of hand strength [ 14 ]. In addition, another study demonstrated that low-intensity, short-duration handgrip exercise produces significant elevations in blood pressure [ 13 , 15 ]. Furthermore, such isometric handgrip exercise can mobilize the muscles of hand exercise, which has been found to be beneficial for reducing resting arterial pressure in hypertensive individuals [ 16 ].…”
Section: Introductionmentioning
confidence: 99%